Pengaruh Persepsi Dukungan Organisasi dan Lingkungan Kerja serta Kompensasi Finansial Terhadap Kinerja Karyawan di Dealer Honda M. Yamin Kota Samarinda - Alzahra Zharifa Erwandha; Tetra Hidayati (Indo Publishing, 2026)
This study aims to analyze the effect of perceived organizational support, work environment, and financial compensation on employee performance at Dealer Honda M. Yamin Samarinda. This research uses a quantitative approach, with the population as well as the sample consisting of all employees using a saturated sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the help of SPSS. The results show that perceived organizational support does not have a significant effect on employee performance. On the other hand, the work environment and financial compensation have a positive and significant effect on employee performance. Simultaneously, all independent variables have a significant effect on employee performance with a fairly strong relationship level. These findings indicate that improving the quality of the work environment and providing fair and adequate financial compensation are important factors in enhancing employee performance. Meanwhile, perceived organizational support has not become a dominant factor in improving employee performance at Dealer Honda M. Yamin Samarinda. This study implies that companies should focus more on improving the work environment and compensation systems to increase employee productivity.